Events of corrosion phenomena on carbon steel pipes in environment of sea water and ammonia solutions due to the presence of sweet gas - Nendi Suhendi Syafei (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
Based on the results of the study that the test sample material using carbon steel pipe plate API 5L-X65 is in chamber. With the research using the three point loading method is the environment of CO2 gas and saturated H2S gas in a solution of 7900 ml of sea water and 100 ml ammonia, the corrosion phenomenon occurs. And the corrosion event that occurs, is stress corrosion cracking transgranular and intergranular based the results of microstructure test results and based the results of polarized microscopy test. The corrosion rate that occurs will increase with the deflection given to the larger test samples for the same exposure time, the corrosion rate that occurs will increase with the stress σ given to the test sample getting larger for the same exposure time and inside crack will get deeper with the deflection given to the test sample getting larger for the same exposure time.